2017
DOI: 10.1111/jfpe.12606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of falling‐film freeze concentration on bioactive compounds in aqueous coffee extract

Abstract: Falling‐film freeze concentration (FFFC) is a technology used to concentrate liquids by freezing. This study demonstrated the effect of FFFC on bioactive compounds in coffee extract and their antioxidant activity. Coffee extract containing 5% solids was freeze‐concentrated in 2 successive steps. The main bioactive compounds, chlorogenic acids and caffeine were detected by RP‐HPLC. The antioxidant activity and phenolic content were assessed by ABTS, DPPH, and Folin–Ciocalteu assays. The solution was concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
(89 reference statements)
7
13
0
Order By: Relevance
“…As mentioned above, this behavior could be associated with the use of low temperatures in CBCC to concentrate bioactive compounds, since the damage to the sensitive components is minimal and, therefore, this process allows a higher anthocyanin concentration than other concentration technologies. A similar trend was observed by Correa et al [39] and Silva et al [40] during the freeze concentration of coffee extract and apple juice, respectively.…”
Section: Bioactive Compound Content and Antioxidant Activity Determinsupporting
confidence: 87%
See 2 more Smart Citations
“…As mentioned above, this behavior could be associated with the use of low temperatures in CBCC to concentrate bioactive compounds, since the damage to the sensitive components is minimal and, therefore, this process allows a higher anthocyanin concentration than other concentration technologies. A similar trend was observed by Correa et al [39] and Silva et al [40] during the freeze concentration of coffee extract and apple juice, respectively.…”
Section: Bioactive Compound Content and Antioxidant Activity Determinsupporting
confidence: 87%
“…Hence, the cryoconcentrated samples presented an increase up to 3.4 (TPC), 3.0 (TFC), and 2.8 (TFLC) times compared to the initial value. This tendency has been observed with liquid samples such as orange juice [14], strawberry juice [15], blueberry juice [17], pineapple juice [19], yerba mate [38], and coffee extract [39] obtained by the various CC techniques.…”
Section: Bioactive Compound Content and Antioxidant Activity Determinmentioning
confidence: 64%
See 1 more Smart Citation
“…The fresh juice group had the highest amount of volatile compounds, and the areas corresponded with twelve esters, three acids, three alcohols, three ketones, three aldehydes, and two unknown compounds. Several authors reported that esters are the major volatile compounds in pineapple and may contribute to the pronounced fruity aroma, although their qualitative and quantitative composition may differ among the analyzed samples .…”
Section: Resultsmentioning
confidence: 99%
“…[6,[18][19][20] Recent research has investigated these parameters applying freeze concentration to various food products, such as for example apple juice, dairy and coffee extract. [21][22][23][24][25] A common problem is that with increased product concentration, the viscosity of most concentrates will increase. This increase in viscosity will hinder mass transfer of solutes from the boundary layer to the bulk and therefore enhance solute inclusion.…”
Section: Introductionmentioning
confidence: 99%